2019
DOI: 10.4236/jss.2019.711005
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Stakeholders and the Use of Corporal Punishment as a Tool for Discipline in Public Secondary Schools, Western Region of Kenya

Abstract: Since the beginning of this century, a global tendency to abolish corporal punishment has been introduced to challenge old dependence on corporal punishment as a tool for reforming children's misbehavior. This tendency was highly supported by the contemporary call for protecting human rights including the right in security and human treatment and child rights in physical protection. Corporal punishment continues to be practiced at unacceptable rates in Kenyan schools; at the same time violence rates are rising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Such research is particularly relevant because of the prevalence of child trauma in Somali refugee samples. Corporal punishment is common in Somali schools, indicating that Somali refugees have likely experienced this form of child trauma (Mutiso et al, 2019; Najoli et al, 2019). Research is needed to explore the impact of this childhood trauma, as well as general child maltreatment, on Somali refugee mental health.…”
Section: The Impact Of Child Trauma On Somali Refugeesmentioning
confidence: 99%
“…Such research is particularly relevant because of the prevalence of child trauma in Somali refugee samples. Corporal punishment is common in Somali schools, indicating that Somali refugees have likely experienced this form of child trauma (Mutiso et al, 2019; Najoli et al, 2019). Research is needed to explore the impact of this childhood trauma, as well as general child maltreatment, on Somali refugee mental health.…”
Section: The Impact Of Child Trauma On Somali Refugeesmentioning
confidence: 99%
“…The management of children's behavior problems is a major challenge for many school teachers. Teachers need to find a balance between the difficulty in disciplining students and respecting the students' human rights (Najoli, Runhare, & Ouda, 2019). Minor students are persons without or with limited capacity for criminal responsibility.…”
Section: The Act Of Counterattack Against the Illegal Infringement Of...mentioning
confidence: 99%
“…A study by Najoli et al, (2019) established that, forbidding of the cane undermined discipline in schools. The study found out that cases of indiscipline in schools were on the increase after corporal punishment was withdrawn.…”
Section: Introductionmentioning
confidence: 99%